Rainbow connection number of corona product of graphs - Septyanto, Fendy (Electronic Journal of Graph Theory and Applications (EJGTA), 2024)
In an edge-colored graph (where adjacent edges may have the same color), a rainbow path is a path whose edge colors are all distinct. The coloring is called a rainbow coloring if any two vertices can be connected by a rainbow path. The rainbow connection number rc(G) is the smallest number of colors in a rainbow coloring of G. The corona product G ∘ H of two graphs G and H is constructed from one copy of G and n = |V (G)| disjoint copies of H such that the i-th vertex of G is joined to all vertices in the i-th copy of H, for each i ∈{1,…,n}. Several resuls on the rainbow connection number of corona product have been published, but there are inaccuracies. In this paper, we close the gaps and add new results. The strong variant of rainbow connection number is also discussed.